Comparative Analysis on Efficiency of Rural Bank and Islamic Rural Bank in Yogyakarta - Mimma Maripatul Uula; Annisa Kartika Ocktavia; Muhammad Zulva Zeta Zaidan (SMART Insight, 2023)
This research aims to ascertain the efficiency levels of BPRs (Rural Banks) and BPRSs (Islamic Rural Banks) within the province of D.I. Yogyakarta. The sample utilized in this study comprises 49 BPR and 12 BPRS situated in D.I. Yogyakarta, spanning the research period of 2017-2021. The analytical approach employed is the non-parametric Data Envelopment Analysis (DEA), utilizing secondary data sourced from bank financial reports. The determination of input and output variables in this study adopts an intermediary approach. The input variables encompass fixed assets, operational expenses, and third-party funds, while the output variables encompass the quantity of disbursed financing and operational income.The findings of this research reveal a fluctuating trend within BPRs and BPRSs in Yogyakarta over the course of years. Based on the CRS (Constant Returns to Scale) and VRS (Variable Returns to Scale) scores, it is discernible that the efficiency levels of both BPRs and BPRSs experienced a reduction during the Covid-19 pandemic. The study's insights have the potential to stimulate informed decision-making and policy refinement, ultimately fostering a more robust financial sector and bolstering economic recovery efforts in the post-Covid-19 landscape.